El uso del material didáctico en el proceso enseñanza aprendizaje de las ciencias naturales de los estudiantes del octavo, noveno y décimo año de educación general básica del colegio fiscal Amazonas del cantón y provincia de Zamora Chinchipe período 2012 - 2013. Lineamientos alternativos - Gutierrez Bautista, Leidy Karina (2013)
The didactic materials are those assistants that facilitate the teaching process - learning, inside a global educational context, they stimulate the function of the senses so that the students consent with more easiness to the information, acquisition of abilities and dexterities, and to the formation of attitudes and values. In this mark he is carried out the titled investigation: "The use of the didactic material in the process teaching - learning of the natural sciences of the students of the eighth, ninth and tenth year of basic general education of the school fiscal amazons of the canton and county of Zamora Chinchipe period 2012-2013", he has as objective to analyze the use of the didactic material in the Process Teaching - Learning of the Natural Sciences of the students of the Eighth, Ninth and Tenth year of Basic General Education. The present investigation one worked with the whole population in the following way: 18 students of eighth, 17 of ninth, 15 of tenth year of Basic General Education and 3 educational of Natural Sciences. The methods that contributed in this process were: explanatory method, descriptive method, deductive method, inductive method, statistical method and bibliographical method. The techniques that were used were the survey, directed to students and educational of eighth, ninth and tenth year of Basic General Education with the purpose of obtaining empiric information. With the analysis, discussion and interpretation of these data was proven that 100% of the educational ones doesn't frequently use the didactic material for the process teaching learning of the natural sciences for the nonexistence of this resource in the educational institution.